Apple Watch-guided diagnosis of AVNRT in a pregnant woman—A case report and literature review - Hawryszko, Maja; Sławiński, Grzegorz; Kozłowski, Dariusz; Lewicka, Ewa (Frontiers in Cardiovascular Medicine, 2022)
Cardiac arrhythmias occurring during pregnancy pose a therapeutic problem as antiarrhythmic drugs can be potentially harmful to the fetus. A 35-year-old woman in the 20th week of pregnancy was admitted to the Department of Cardiology due to the first episode of arrhythmia in her life. During the event, the patient was wearing an Apple Watch Series 6, which records a 30-second single-channel ECG. The recording showed narrow QRS complex tachycardia of 216 bpm, and short RP interval and atrioventricular nodal reentrant tachycardia (AVNRT) was recognized. Due to the mild nature of the arrhythmia, antiarrhythmic pharmacotherapy was not initiated. The use of mobile health (mHealth) devices such as wearables and health monitoring applications is now a valuable addition to routine cardiac diagnostics for patients of all ages and levels of cardiovascular risk.